A Quantitative Study of Intracranial Calcification in Dementia of the Alzheimer Type - Friedland, Robert P.; Luxenberg, Jay S.; Koss, Elisabeth (International psychogeriatrics, 1990)
Abnormalities in calcium homeostasis have been reported in Alzheimer's disease (AD) and in the neurofibrillary tangle disorders of amyotrophic lateral sclerosis and parkinsonism-dementia occurring in the Pacific. In order to more fully evaluate calcium physiology in AD, we analyzed the size of pineal and choroid plexus calcifications, using X-ray computed tomography, in 23 patients with probable AD and 18 healthy age-matched control subjects. The area occupied by calcification was measured from hard copies of the data by two independent observers who were blind to the diagnosis. There were no differences in the areas occupied by pineal or choroid plexus calcifications between the two groups. These data suggest that AD is not accompanied by alternations in intracranial calcium deposition in pineal gland or choroid plexus.